On the 3D Nature of the Magpie (Aves: Pica pica) Functional Hindlimb Anatomy During the Take-Off Jump - Meilak, E. A.; Gostling, N. J.; Palmer, C.; Heller, M. O. (Frontiers in Bioengineering and Biotechnology, 2021)
Take-off is a critical phase of flight and many birds jump to take to the air. Although actuation of the hindlimb in terrestrial birds is not limited to the sagittal plane and considerable non-sagittal plane motion has been observed during take-off jumps, how the spatial arrangement of hindlimb muscles in flying birds facilitates such jumps has received little attention. This study aims to ascertain 3D hip muscle function in the magpie (Pica pica), a bird known to jump to take off. A musculoskeletal model of the magpie hindlimb was developed using μCT scans (isotropic resolution of 18.2µm) to derive bone surfaces while 3D muscle path definition was further informed by the literature. Function was robustly characterised by determining the 3D moment generating capacity of 14 hip muscles over the functional joint range of motion during a take-off leap considering variations across the attachment areas and uncertainty in dynamic muscle geometry. Ratios of peak flexion-extension (FE) to internal-external rotation (IER) and ab-adduction (ABD) MGC were indicators of muscle function. Analyses of 972 variations of the 3D muscle paths showed that 11 of 14 muscles can act as either flexor or extensor, while all 14 muscles demonstrated the capacity to act as internal or external rotators of the hip with the mean ratios of peak FE to IER and ABD moment generating capacity were 0.89 and 0.31, respectively. Moment generating capacity in IER approaching levels in FE moment generating capacity determined here underline that avian hip muscle function is not limited to the sagittal plane. Together with previous findings on the 3D nature of hindlimb kinematics our results suggest that musculoskeletal models to develop a more detailed understanding of how birds orchestrate the use of muscles during a take-off jump cannot be restricted to the sagittal plane.